Yield Response of Maize (Zea mays L.) Cultivars under Rainfed Condition - Jami, Nzanbeni N.; Singh, P. L.; Nongmaithem, D. (International Journal of Bio-resource and Stress Management, 2017)
A field experiment was carried out during kharif season of 2013 at Agronomy Research farm, SASRD, Nagaland University, Medziphema under rainfed condition to study the performance of different maize cultivars. The experiment was laid out in RBD. The treatments of the experiment were comprised of ten maize cultivars viz, DHM-117 (Hybrid), Vijay (Composite), RCM-75 (Composite), RCM-76 (Composite), DA.61-A (Composite), Epok Tsungaro (Local), Elong Tsungaro (Local), Ekyuv Tsungaro (Local), Mhapho (Local) and Mengya (Local). The results of the experiment revealed that cultivar RCM-76 was the fastest growing among all the maize cultivars tested which recorded the tallest plant height, maximum number of green leaves plant-1, highest stem thickness, highest leaf are index, highest crop growth rate and maximum shoot dry weight. The same cultivar was also found to obtain maximum value of yield attributing characters viz., No. of cobs plant-1, cob diameter, cob length and test weight and ultimately produced the highest grain yield (5576.72 kg ha-1) along with highest stover yield (8856.67 kg ha-1). Highest gross return (` 83651 ha-1), net return (` 58311 ha-1) and benefit cost ratio (2.3) was recorded with RCM-76 which was followed by DHM-117 with benefit cost ratio of 2.1. Among all the tested cultivars, local cultivar Epok Tsungaro obtained lowest value in growth and yield attributes and produced the lowest grain yield (1293.65 kg ha-1) which gave negative benefit cost ratio of -0.2.